If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 48x + 3 = 50x + -1 Reorder the terms: 3 + 48x = 50x + -1 Reorder the terms: 3 + 48x = -1 + 50x Solving 3 + 48x = -1 + 50x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-50x' to each side of the equation. 3 + 48x + -50x = -1 + 50x + -50x Combine like terms: 48x + -50x = -2x 3 + -2x = -1 + 50x + -50x Combine like terms: 50x + -50x = 0 3 + -2x = -1 + 0 3 + -2x = -1 Add '-3' to each side of the equation. 3 + -3 + -2x = -1 + -3 Combine like terms: 3 + -3 = 0 0 + -2x = -1 + -3 -2x = -1 + -3 Combine like terms: -1 + -3 = -4 -2x = -4 Divide each side by '-2'. x = 2 Simplifying x = 2
| -1.8m-27=-4.8-6 | | 3x^2+4x=x(-7x+8) | | 7(6x+10)=42x-4 | | 5x+5(4)=15 | | 16x+10(18-x)=240 | | logx+log(4x)=2 | | 6h-2=4h+12 | | -2(x-5)=17 | | 16+p=5 | | 10+6x=5+x | | y-9=17 | | 12+2x+x=9x+6 | | 5b+19=-11 | | f(x)=9x^4+27x^3-13x^2-12x+4 | | 5x-28+18x-53+y+11=117 | | X-(-4)+x=14 | | 5x-28+18x-53+117=y+11 | | 38=3x+14 | | 5-9x=-31 | | 6k-7=-43 | | 3(x+8)=x-4 | | 7+6m=-89 | | 245(31/2)= | | 17x=7x+37 | | 12x^2-36= | | 3+u=-2 | | -5p=2 | | 22(-4h--13)=37+13h | | 2x+3-7x=18 | | 2.1(4.6+1.3y)=10.68-18.32 | | 4d-7=5d | | F(t)=-2t+2 |